Recording of the clinical characteristics of critically ill patients attended the ED of Provincial Hospital - Sofia Zyga; Evgenia-Sotiria Spyridakou; Evangelos Fradelos; Victoria Alikari (Ene, 2017)
Introduction: The invasive mechanical ventilation and non invasive mechanical ventilation is, nowadays, an important treatment procedure for critically ill patients. Aim: the detection of clinical characteristics and outcome of critically ill patients who undergone invasive or non-mechanical ventilation in the Emergency Department of a Provincial Hospital in Peloponnese. Results: On the total132 patients who underwent invasive or noninvasive mechanical ventilation were recorded. Eighty two(62.1%) were males and 48 (36.3%) females. Of these, 52 (39.4%) were diagnosed with Traumatic Brain Injury (TBJ), 20 (15.2%) with coronary heart disease and 18 (13.6%) with respiratory insufficiency. Invasive mechanical ventilation was applied in 75 (56.8%) patients while non-invasive mechanical ventilation was applied in 6 (4.4%).Regarding the outcome, death occurred in the ED for 88 (66.7%) patients, 30 (22.7%) were transferred to ICU and seven (5.3%) were hospitalized in Department of Internal Medicine. Also, a significant correlation (p = <0,001) was found between outcome and gender as, of the 30 patients who were transferred to ICU, 22 (73.3%) were male. Futhermore, it can be proven by thefact that of the 88 patients that died, 54 (61.3%) were also men ( p = <0.001).Conclusions: This study revealed the high numbers of patients undergoing invasive or non-mechanical ventilation at local level, in the Emergency Department of a Provincial Hospital.